ANALISIS PERBANDINGAN ARUS JENUH PADA PENDEKAT SIMPANG TERLINDUNG DAN TERLAWAN DENGAN METODE MKJI DAN METODE TIME SLICE (STUDI KASUS: SIMPANG SUBITA DAN SIMPANG WARIBANG) - I Made Kariyana; Gede Sumarda; I Gede Aryanta Putra (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
As many as 33% of vehicle ownership in Bali Province in 2019 was in Denpasar City, coupled with the passing of vehicles from outside the city to work and recreation to burden the road network in Denpasar City. This causes problems in the transportation system that affects the performance of the road network, especially the performance of signalized intersection in Denpasar City. The performance of the signalized intersection is affected by the capacity of the approach where one of the factors that affect it is saturation flow. This study aims to find out the comparison of saturation flow in protected and opposed approach between the IHCM and Time Slice Method. The saturation flow result in the protected approach in Simpang Subita based on IHCM is 3,629 pcu/green hours greater than 71.18% compared to the Time Slice Method which is 2,120 pcu/green hours, while the saturation flow result in the opposed approach in Simpang Waribang based on IHCM is 1,857 pcu/green hour smaller than 37.49% compared to the Time Slice Method which is 2,971 pcu/green hour.